Star Wars. Episode VII, The Force awakens [videorecording (Blu-Ray)] - Lucas, George, 1944- (Lucasfilm Ltd, 2019)
As Kylo Ren and the sinister First Order rise from the ashes of the Empire, Luke Skywalker is missing when the galaxy needs him most. It's up to Rey, a desert scavenger, and Finn, a defecting stormtrooper, to join forces with Han Solo and Chewbacca in a desperate search for the one hope of restoring peace to the galaxy.